Relation of the of articular eminence inclination with morphological alterations of temporomandibular condylars - Calle Velezmoro, Eduardo Miguel (2017)
Objective: To determine the relationship between the inclination of the articular eminence and the presence of morphological alterations of the temporomandibular condyles. Materials and methods: We studied 91 patients (182 temporomandibular joints) convex-beam volumetric tomograms belonging to patients of the Radiology Service of the Clinic Specialized in Dentistry of the San Martin de Porres University from 2014 to 2016. Results: When we have a value p <0.01 we can see that there is a relation of the inclination of the articular eminence with the morphological alterations of this eminence. Conclusions: Exist morphological alterations of the articular eminence only with the inclination of the posterior slope of this eminence. Key words: Mandibular Condyle, temporomandibular joint. (Source: MeSH NLM)